AWARENESS AND KNOWLEDGE ABOUT SPEECH -LANGUAGE PATHOLOGY IN MBBS STUDENTS - Adhikary, Anil Kumar; Bhattarai, Bebek (Nepalese Journal of ENT Head & Neck Surgery, 2018)
Objectives: The aim of the study is to investigate the level of awareness and knowledge of Speech Language Pathology among MBBS students in Province Three of Nepal. Materials and methods: A descriptive cross sectional study was carried out. It was carried out in December 2017 among medical students. Only the colleges having speech language pathologists working as a academician were included in the study. The study was carried out by distributing the questionnaire developed by Breadner with slight modification to reflect the Nepali culture. Statistical analysis was carried out with the help of SPSS software version 25. Results: Among 119 MBBS students 63.90 % were male and 36.10 % were female. Majority of the students had never heard about Speech-Language Pathology and only few reported to know speech language pathologists’ (SLP) works and the population with whom SLPs work. The major source of information about this new field was from “Friends “. Few reported to know SLPs as a part of their hospital staff and also as their teaching faculty. Conclusion: Limited interaction of students with Speech-language Pathologist might be a strong reason for very little awareness and knowledge about Speech-language pathology field. Keywords: Awareness, MBBS students, Speech disorders, Speech Language Pathologists, Speech therapy